2021
DOI: 10.1186/s12889-021-11149-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of mitigation policies and socioeconomic status on COVID-19 prevalence and social distancing in the United States

Abstract: Background The spread of COVID-19 has highlighted the long-standing health inequalities across the U.S. as neighborhoods with fewer resources were associated with higher rates of COVID-19 transmission. Although the stay-at-home order was one of the most effective methods to contain its spread, residents in lower-income neighborhoods faced barriers to practicing social distancing. We aimed to quantify the differential impact of stay-at-home policy on COVID-19 transmission and residents’ mobility… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 38 publications
4
13
0
Order By: Relevance
“…The COVID-19 pandemic has had a range of impacts, and populations with the poorest socioeconomic status have been the most affected. Populations with the greatest deprivation (measured according to the MEDEA index), have a lower percentage of flu vaccination and a greater probability of presenting with COVID-19, apparently consistent with results published by some authors (Mena et al, 2021; Riou et al, 2021; Hawkins et al, 2020; Chang et al, 2021; Morrissey et al, 2021). This relationship may be due to the fact that the highest levels of deprivation include the worst socioeconomic conditions, housing characteristics, types of employment and access to education and culture.…”
Section: Discussionsupporting
confidence: 88%
“…The COVID-19 pandemic has had a range of impacts, and populations with the poorest socioeconomic status have been the most affected. Populations with the greatest deprivation (measured according to the MEDEA index), have a lower percentage of flu vaccination and a greater probability of presenting with COVID-19, apparently consistent with results published by some authors (Mena et al, 2021; Riou et al, 2021; Hawkins et al, 2020; Chang et al, 2021; Morrissey et al, 2021). This relationship may be due to the fact that the highest levels of deprivation include the worst socioeconomic conditions, housing characteristics, types of employment and access to education and culture.…”
Section: Discussionsupporting
confidence: 88%
“…The GDP per capita coefficient is also positive but is significant only for El Salvador. This finding confirms the critical role of socio-economic attributes in NPIs adherence reported in previous works [11,13,[53][54][55]. Looking at sociodemographic features, we find that both population and density have a positive significant coefficient in all countries.…”
Section: Regression Analysissupporting
confidence: 91%
“…They concluded that incidences were higher in more affluent populations in the first wave of the pandemic but inverted with ongoing progression, manifesting in higher rates in socioeconomically disadvantaged populations in waves 2 and 3. Chang et al, Neelon et al, and Clouston et al investigated infection rates in the US and found similar results at the county level [ 13 , 36 , 58 ]. Furthermore, Neelon et al showed sinusoidally shaped temporal dynamics of socioeconomic inequalities in COVID-19 incidence, indicating several crossovers over time [ 58 ] similar to one study from the UK [ 65 ].…”
Section: Resultsmentioning
confidence: 80%
“…However, when mobility restrictions were implemented, populations in lower-paid occupations, precarious jobs, and those living in higher-density housing or using public transport may have been less able to maintain physical distancing, while better-off populations tend to have more resources to follow infection protection restrictions, such as the ability to work remotely [ 13 , 36 , 42 – 44 , 49 , 60 , 66 , 74 ]. Furthermore, populations of lower education may have had insufficient information about the pandemic situation.…”
Section: Discussionmentioning
confidence: 99%